2010
DOI: 10.1053/j.gastro.2009.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Gender Dimorphic Formation of Mouse Mallory–Denk Bodies and the Role of Xenobiotic Metabolism and Oxidative Stress

Abstract: BACKGROUND AND AIMS-Mallory-Denk bodies (MDBs) are keratin (K)-rich cytoplasmic hepatocyte inclusions commonly associated with alcoholic steatohepatitis. Given the significant gender differences in predisposition to human alcohol-related liver injury, and the strain difference in mouse MDB formation, we hypothesized that gender affects MDB formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 45 publications
5
52
0
Order By: Relevance
“…Similarly, the presence of nuclear lamin or cytoplasmic keratin aggregates (not inclusions per se, presumably due to the smaller-sized aggregates as compared to inclusions seen by standard hematoxylin and eosin staining) has been reported in several laminopathies (Dechat et al, 2008;Bertrand et al, 2011;Worman, 2012) and in the setting of epidermal keratin mutation in the Dowling-Meara form of epidermolysis bullosa simplex (Coulombe et al, 1991). Our findings demonstrate for the first time the presence of nuclear lamin aggregates in the absence of lamin mutation but in response to porphyria-mediated liver injury, which also reflects an oxidative form of liver injury (Hanada et al, 2010;Snider et al, 2011). Our findings are not able to distinguish whether lamin aggregation takes place en-route to the nucleus or directly in the nucleus.…”
Section: Lamin-containing Aggregates Form In the Context Of Liver Injurymentioning
confidence: 53%
“…Similarly, the presence of nuclear lamin or cytoplasmic keratin aggregates (not inclusions per se, presumably due to the smaller-sized aggregates as compared to inclusions seen by standard hematoxylin and eosin staining) has been reported in several laminopathies (Dechat et al, 2008;Bertrand et al, 2011;Worman, 2012) and in the setting of epidermal keratin mutation in the Dowling-Meara form of epidermolysis bullosa simplex (Coulombe et al, 1991). Our findings demonstrate for the first time the presence of nuclear lamin aggregates in the absence of lamin mutation but in response to porphyria-mediated liver injury, which also reflects an oxidative form of liver injury (Hanada et al, 2010;Snider et al, 2011). Our findings are not able to distinguish whether lamin aggregation takes place en-route to the nucleus or directly in the nucleus.…”
Section: Lamin-containing Aggregates Form In the Context Of Liver Injurymentioning
confidence: 53%
“…The formation of cytoplasmic aggregates in this model is relevant, because IFs are major components of intracellular inclusions seen in several human diseases, including the K8/K18-containing Mallory-Denk bodies that are primarily seen in hepatocytes of patients with steatohepatitis and hepatocellular carcinoma, among other liver diseases (33,38). Examination of the livers of DDC-fed mice, which form human Mallory-Denk body-like inclusions (25,38) suggested that there is no significant localization of SUMO within Mallory-Denk bodies. 3 In light of the study by Kaminsky et al (10) and our current results demonstrating that modest sumoylation increases K8 solubility (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the effect of 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC)-induced liver injury (after a 90-day DDC treatment) on sumoylation, the livers of FVB/N female mice were used as described (25). To determine the effect of the phosphatase inhibitor microcystin LR (MLR) on sumoylation, human K18-overexpressing mice (26) were injected with 30 g/kg of MLR intraperitoneally followed by harvesting of the livers after 195 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For in vivo oxidative liver damage, mice were fed with a hepatotoxin 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) diet for 3 weeks to induce chronic oxidative stress in the liver (29).…”
Section: Methodsmentioning
confidence: 99%